Uzņēmuma IT vides uzlabošana - Pūgulis, Jānis (Latvijas Universitāte, 2012)
Kvalifikācijas darba tēma ir “Uzņēmuma IT vides uzlabošana”. Darba mērķis ir izpētīt uzņēmuma IT infrastruktūru un uzlabot informācijas sistēmu un drošību uzņēmumā kopumā. Darba uzdevumi ir jaunu risinājumu ieviešana, esošās sistēmas sakārtošana un uzlabošana. Rezultātā tika sakārtota un uzlabota uzņēmuma IT vide, paaugstinot tās drošību, ieviešot jaunas sistēmas, jaunus risinājumus kā arī uzlabojot vecos.

Qualification paper title is “IT infrastructure improvement in a company”. The aim for this paper is to explore IT infrastructure in the chosen company and to improve information system over all and security in the company. Paper objectives are: introduction of new solutions, optimizations and finding possible improvements in the existing system. In the end, the goals for optimization and increased safety were met, as the introduction of the new system and solutions, fulfilled the necessary requirements for improving the current system.
IT infrastructure improvement in a company
Keywords: Datorzinātne